Effects of Tai Chi Softball Exercises on Physical Fitness Level and Cardiovascular Health-Related Factors among Older Females. (3rd July 2021) - Cheng, XiaoDong; Fan, Yongzhao; Ge, Ling; Zang, Desen; Li, Jianxi; Li, Jian; Wu, Hao
Abstract : Tai Chi softball was voted as one of the most popular health-promoting exercises and can also develop manipulative skill and hand-eye coordination. The purpose of this study was to explore changes in the physical fitness level and cardiovascular health-related factors after the 16-week Tai Chi softball (TCSB) training program among older females. One hundred healthy older females were assessed at the baseline before TCSB training, and then, they conducted intervention experiments. Through the 16-week TCSB intervention training, a control group and a physical exercise group showed significant differences. The physical exercise group significantly reduced body mass index, systolic blood pressure, and diastolic blood pressure from all the results studied. It also reduces total cholesterol, triglycerides, low-density lipoprotein cholesterol ( ∗ p < 0.05 ), and waist-to-hip ratio ( ∗ ∗ p < 0.01 ), whereas handgrip, sit and reach, single leg stance, vital capacity ( ∗ p < 0.05 ), and high-density lipoprotein cholesterol ( ∗ ∗ p < 0.01 ) were significantly increased. TCSB training may improve physical fitness ability and decrease the risk of cardiovascular disease among older females.